Quersetin Pada Benalu Teh Sebagai Terapi Hipertensi - Syfa Dinia Putri (Medula, 2020)
Hypertension is still a big challenge in world. This disease is sometimes not realized by the sufferer. Hypertension is known by increased systolic blood pressure greater than 140 mmHg and / or diastolic greater than 90 mmHg on two measurements with an interval of 5 minutes in a state of resting enough (calm). The management of hypertension can be done by using drugs or by modifying lifestyle. Treatment of hypertension can be done using traditional medicines. Various studies have shown that tea parasites can lower blood pressure because tea parasites contain flavonoids. One of the powerful flavonoids is quercetin. These compounds act as antioxidants by releasing or donating hydrogen ions to peroxy free radicals to make them more stable. This activity blocks the oxidation reaction of bad cholesterol (LDL) which causes blood to thicken, thus preventing the deposition of fat on the walls of blood vessels. Quercetin also has the potential to increasing Nitric Oxide (NO) production in endothelial cells. In this case, the tea parasite containing quercetin is thought to have an effect on lowering blood pressure. So the parasite tea can be used as an antihypertensive.